2018
DOI: 10.33383/2018-003
|View full text |Cite
|
Sign up to set email alerts
|

Effective Radiant Flux for Non-image Forming Effects – is the Illuminance and the Melanopic Irradiance at the Eye Really the Right Measure

Abstract: Research indicates that intrinsically photosensitive Retinal Ganglion Cells are not evenly distributed or evenly sensitive throughout the retina. Still, most research looking into non-image forming (NIF) effects uses an integral measured quantity, illuminance or melanopic weighted irradiance, to represent the amount of light at the participantsХ eye level. This paper describes a theoretical approach to define the effective radiant flux for stimulating the ipRGCs, taking into account a spatially resolved sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…In addition, Rea et al showed that the level of nocturnal melatonin suppression caused by a homogeneous full-field illumination of the same 100 photopic lux at the cornea was not significantly different from what would be expected when averaging over the four hemi-fields. Finally, Knoop et al [29,30] based on theoretical considerations showed that, by assuming a nonuniform distribution of the retinal photoreceptors contributing to non-visual effects, lighting conditions of equal vertical illuminance and equal melanopic irradiance at the cornea may still cause very different integrated receptor signals that eventually result in distinct non-visual outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Rea et al showed that the level of nocturnal melatonin suppression caused by a homogeneous full-field illumination of the same 100 photopic lux at the cornea was not significantly different from what would be expected when averaging over the four hemi-fields. Finally, Knoop et al [29,30] based on theoretical considerations showed that, by assuming a nonuniform distribution of the retinal photoreceptors contributing to non-visual effects, lighting conditions of equal vertical illuminance and equal melanopic irradiance at the cornea may still cause very different integrated receptor signals that eventually result in distinct non-visual outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The use of corneal irradiance (radiation density received at the front of the eye) to predict the extent of any non-image forming effect of light is often used as simple way to describe the impact of radiation on people. However, there is no direct experimental evidence to support the concept and the idea has already been questioned by Broszio et al 18 The ideas developed in this paper may call the use of corneal irradiance further into question as logically the arguments put forward in this paper could equally apply when discussing circadian entrainment.…”
Section: Discussionmentioning
confidence: 84%
“…The need for spatially resolved measurements is further illustrated by Broszio et al (2017). In their study, an analysis of lighting conditions was conducted in an LED backlit test room with typical celloffice dimensions (5 m wide, 4 m long, and 2.8 m high) at the Chair of Lighting Technology of Technische Universität Berlin.…”
Section: Spatially Resolved Measurementsmentioning
confidence: 99%
“…At this moment, the spectral radiant incidence could, for example, be weighted with the spectral efficiency functions s α λ ð Þ of each photoreceptor type (CIE 2015 If required, this incidence of luminous or radiant flux can be used to define the NIF effective irradiance. When properly calibrated and combined with fundamentals (2), (3), and (4), a camera image provides information about the contribution of a relevant area A within the field of view to the overall illuminance or α-opic irradiance 2 on a plane (Broszio et al 2017).…”
Section: Analysis For Nif Effectsmentioning
confidence: 99%
See 1 more Smart Citation